Artificial Engineering of Immune Cells for Improved Immunotherapy. Issue 6 (8th April 2021) - Li, Chuxin; Qi, Yongdan; Zhang, Yu; Chen, Yingge; Feng, Jun; Zhang, Xianzheng
Abstract : An immune system is of vital importance for maintaining the host health. Taking advantage of innate merits of immune cells, cell‐based immunotherapy has demonstrated great potentials for treating many severe diseases, especially for cancers and inflammatory diseases. However, the success of this promising therapy modality suffers from complex and immunosuppressive conditions generated along with disease development. The combination among cellular biology, nanotechnology, and material science offers vast opportunities to improve therapeutic efficacy and expand function. This review introduces recent advance in exploiting nanotechnology and materials to initiate and reinforce therapeutic functions of live immune cells, including monocyte, macrophage, dendritic cell, and T lymphocytes. The major strategies in artificially engineered cell immunotherapy are briefly summarized, and the possible developing trend in this field is discussed. Abstract : For disease and tumor treatment, both cell‐based immunotherapy and nanomedicine‐mediated intervention suffer from poor outcomes and even failure. This review summarizes the current strategies that ingeniously combine immune cells with nanomaterials for therapeutic purposes, discusses their novel insights, and forecasts the prospects of artificially engineered cells for biomedical applications.